Dehydrocostus Lactone Suppresses LPS-induced Acute Lung Injury and Macrophage Activation through NF-κB Signaling Pathway Mediated by p38 MAPK and Akt - Yunjuan Nie (Molecules, 2019)
Acute lung injury (ALI) is a severe clinical disease marked by dysregulated inflammation response and has a high rate of morbidity and mortality. Macrophages, which play diverse roles in the inflammatory response, are becoming therapeutic targets in ALI. In this study we investigated the effects of dehydrocostus lactone (DHL), a natural sesquiterpene, on macrophage activation and LPS-induced ALI. The macrophage cell line RAW264.7 and primary lung macrophages were incubated with DHL (0, 3, 5, 10 and 30 μmol/L) for 0.5 h and then challenged with LPS (100 ng/mL) for up to 8 hours. C57BL/6 mice were intratracheally injected with LPS (5 mg/kg) to induce acute lung injury (ALI) and then treated with a range of DHL doses intraperitoneally (5 to 20 mg/kg). The results showed that DHL inhibited LPS-induced production of proinflammatory mediators such as iNOS, NO, and cytokines including TNF-α, IL-6, IL-1β, and IL-12 p35 by suppressing the activity of NF-κB via p38 MAPK/MK2 and Akt signaling pathway in macrophages. The in vivo results revealed that DHL significantly attenuated LPS-induced pathological injury and reduced cytokines expression in the lung. NF-κB, p38 MAPK/MK2 and Akt signaling molecules were also involved in the anti-inflammatory effect. Collectively, our findings suggested that DHL is a promising agent for alleviating LPS-induced ALI.